Superabsorbent polymer film and absorbent article comprising the same
By using a thin superabsorbent polymer film in absorbent products, the problem of wearability deterioration caused by waterproofing of absorbent products is solved, and the external humidity sense and wear comfort are significantly improved, and the balance between moisture absorption and breathability is achieved.
Patent Information
- Application Number
- CN202280004785.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-18
- Filing Date
- 2022-03-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-03-21
AI Technical Summary
The liquid impermeable back sheet of existing absorbent products such as disposable diapers and sanitary napkins is too waterproof, which leads to impermeability of water vapor and air, resulting in deterioration of wearability, and moisture emitted by the absorbent material is transmitted to the outside. Impact user experience.
Using a superabsorbent polymer film with a thickness of 500 μm or less and a moisture absorption rate of 10 g/m2 to 100 g/m2 are laminated between the liquid impermeable backsheet and the breathable waterproof film or between the breathable waterproof film and the absorbent material , improve humidity and breathability.
It significantly reduces external humidity, reduces rash and irritation, and improves wear comfort of absorbent products while maintaining breathability and moisture absorption.
Smart Images

Figure CN115697271B_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2021-0039666, filed on March 26, 2021, in the Korean Intellectual Property Office, and Korean Patent Application No. 10-2022-0034232, filed on March 18, 2022, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present disclosure relates to a superabsorbent polymer film having excellent hygroscopicity, and to an absorbent article excellent in having an improved sense of external wetness by including the superabsorbent polymer film. Background Art
[0004] Absorbent articles such as disposable diapers, sanitary napkins and incontinence pads generally include a liquid-impermeable back sheet, an absorbent material and a liquid-permeable top sheet in contact with the wearer's skin. If necessary, they may also include a breathable waterproof film for improving air permeability, a decorative sheet for improving appearance, and an elastic three-dimensional guard (leg cuff) for improving wearing feel and preventing side leakage.
[0005] In such absorbent articles, a material that allows body fluid to quickly pass through the absorbent material, such as a synthetic polymer nonwoven fabric, is used as a liquid-permeable top sheet. The absorbent material is made of superabsorbent polymer, pulp, tissue paper or nonwoven fabric, and plays a role in quickly absorbing and retaining body fluid that has passed through the liquid-permeable top sheet. The liquid-impermeable back sheet prevents the body fluid absorbed by the absorbent material from leaking, and a woven or nonwoven fabric made of natural fibers or synthetic fibers is used.
[0006] Liquid-impermeable backsheets are basically designed to be waterproof, but when the waterproofness is too good, water vapor and air are not permeable, so there is a problem of wearability degradation. Therefore, liquid-impermeable backsheets are usually made of moisture-permeable waterproof woven or nonwoven fabrics, which have holes of a size that are impermeable to water particles and permeable to smaller water vapor particles. However, due to the moisture permeability of the backsheet, the moisture emitted from the absorbent material is transferred to the outside of the backsheet. Therefore, when worn for a long time, moisture is felt even on the outside of the absorbent article, which makes the feeling during use worse. Summary of the invention
[0007] Technical issues
[0008] In order to solve the above problems, provided are a thin superabsorbent polymer film having excellent hygroscopicity, and an absorbent article having improved external humidity by including the superabsorbent polymer film.
[0009] Technical Solution
[0010] According to one embodiment of the present disclosure, there is provided a super absorbent polymer film having a thickness of 500 μm or less and a 10 g / m 2 Up to 100g / m 2 Moisture absorption rate.
[0011] The thickness of the super absorbent polymer film may be 10 μm to 200 μm.
[0012] The super absorbent polymer film may have a water content of about 1% to about 15% and a tensile strength of about 5 MPa to about 50 MPa.
[0013] According to another embodiment of the present disclosure, an absorbent article is provided, the absorbent article comprising a liquid-impermeable back sheet; a breathable waterproof film; an absorbent material comprising superabsorbent polymer powder and pulp; and a liquid-permeable top sheet, wherein a superabsorbent polymer film is included between the liquid-impermeable back sheet and the breathable waterproof film and / or between the breathable waterproof film and the absorbent material, and the superabsorbent polymer film has a thickness of 500 μm or less and a weight of 10 g / m2 measured according to KS F2611 standard. 2 Up to 100g / m 2 Moisture absorption rate.
[0014] The thickness of the super absorbent polymer film may be 10 μm to 200 μm.
[0015] The superabsorbent polymer film may be laminated on one side of the liquid-impermeable backsheet; and / or laminated on one or both sides of the breathable waterproof membrane.
[0016] For example, a superabsorbent polymer film is laminated on one side of a breathable waterproof film, and the air permeability of the laminated superabsorbent polymer film and the breathable waterproof film may be 3000 g / m 2 24 hours to 5000g / m 2 ·24 hours.
[0017] The liquid-impermeable back sheet may be a nonwoven fabric having a pore size of 20 μm to 1000 μm.
[0018] The air permeability of the breathable waterproof membrane can be 2000g / m 2 24 hours to 5000g / m 2 ·24 hours.
[0019] The absorbent material may comprise from 10% to 90% by weight of superabsorbent polymer powder.
[0020] The liquid permeable topsheet may have a basis weight of 15 g / m 2 Up to 30g / m 2 .
[0021] Beneficial Effects
[0022] The superabsorbent polymer film of the present disclosure is very thin and has excellent hygroscopicity, so it can be applied to products that require a hygroscopic function. In addition, the absorbent article of the present disclosure includes a superabsorbent polymer film in addition to the absorbent material, so that the external sense of humidity is significantly reduced. Therefore, rashes and other irritations generated when the absorbent article is warmed by the body of the wearer can be reduced, and the absorbent article is excellent in terms of feel. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a cross-sectional view showing the configuration of a conventional absorbent article.
[0024] Figures 2 to 4 is a cross-sectional view showing the configuration of an absorbent article according to one embodiment of the present disclosure. DETAILED DESCRIPTION
[0025] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, the singular form is intended to also include the plural form. It will be further understood that when the terms "include / comprise", "have" or "have" are used in this specification, it is indicated that the features, steps, components or combinations thereof are present, but it does not exclude the presence or addition of one or more other features, steps, components or combinations thereof.
[0026] Since the present invention can be variously modified and has various forms, its specific embodiments are shown by way of example and will be described in detail. However, it is not intended to limit the present invention to the specific form disclosed, and it should be understood that the present invention includes all modifications, equivalents and alternatives within the scope of the thought and technology of the present invention.
[0027] Likewise, the drawings attached to the present disclosure for explaining the present invention are embodiments of the present invention, and the present invention may be presented in various forms and is not limited thereto. In the drawings, parts not related to the description are omitted in order to clearly explain the present invention, and the same reference numerals are used for the same parts throughout the disclosure. In addition, the sizes and relative sizes of the constituent elements shown in the drawings are not related to the actual scale and may be reduced or enlarged for clarity of description.
[0028] Hereinafter, the superabsorbent polymer film of the present disclosure and the absorbent article including the same will be described in detail.
[0029] Super absorbent polymer film
[0030] The super absorbent polymer film according to one embodiment of the present disclosure has a thickness of 500 μm or less and a weight of 10 g / m2 measured according to KS F 2611 standard. 2 Up to 100g / m 2 Moisture absorption rate.
[0031] The superabsorbent polymer film is an acrylic acid-based polymer in the form of a thin film, which is different from existing granular superabsorbent polymers. And it has a water content of 15% or less, is colorless and transparent, has elasticity and exhibits excellent flexibility. The superabsorbent polymer film has no risk of scattering or leaking from an absorbent article during handling, and can be used without an auxiliary agent such as pulp.
[0032] Furthermore, the super absorbent polymer film is thin and has excellent hygroscopicity, so it can be used as a dehumidifier in various products without increasing the bulk or damaging the shape of the products.
[0033] Specifically, the moisture absorption rate of the superabsorbent polymer film can be 10 g / m 2 or larger, 13g / m 2 or larger, 15g / m 2 or larger, or 20g / m 2 or larger, and 100g / m 2 or less or 90g / m 2 The moisture absorption rate can be measured according to KS F2611 standard, and a specific measuring method will be described later in Examples.
[0034] As the thickness of the super absorbent polymer film increases, hygroscopicity may increase, but when it exceeds 500 μm and is too thick, the shape of the article to be applied may be affected. Conversely, when the super absorbent polymer film is too thin, the hygroscopic effect cannot be sufficiently obtained.
[0035] In addition, when the thickness of the superabsorbent polymer film exceeds 500 μm, the air permeability may decrease. However, in the case of a thin superabsorbent polymer film having a thickness of 500 μm or less, when moisture is absorbed, the flexibility of the film is greatly increased, and the capacity between polymer chains is increased, so that hygroscopic properties can be exhibited while ensuring air permeability. Therefore, it can be more suitable for articles requiring both hygroscopicity and air permeability, such as absorbent articles to be described later.
[0036] In view of this, the thickness (h) of the super absorbent polymer film may preferably be 5 μm or more, 10 μm or more, or 15 μm or more, and 400 μm or less, 300 μm or less, 200 μm or less, or 150 μm or less.
[0037] Meanwhile, the water content of the superabsorbent polymer film may be 15 wt % or less, 12 wt % or less, 11 wt % or less, or 10 wt % or less and 1 wt % or more, 2 wt % or more, 4 wt % or more, or 6 wt % or more.
[0038] "Water content" means the amount of moisture contained in a sample relative to the weight of the sample before drying as a percentage. That is, the water content can be calculated by dividing the value obtained by subtracting the weight of the sample after drying from the weight of the sample before drying by the weight of the sample before drying, and then multiplying by 100%. At this time, the drying conditions for measuring the water content are to increase the temperature to about 150°C and maintain it at 150°C, and the total drying time is 20 minutes, including 5 minutes of the heating step.
[0039] The super absorbent polymer film has a thickness of 500 μm or less and a total light transmittance of 89.5% or more relative to visible light, indicating high transparency. The total light transmittance of the super absorbent polymer film according to one embodiment of the present disclosure may be 90% or more, 90.3% or more, 91% or more, 91.5% or more, or 92% or more. The total light transmittance may be 100% in theory, for example, it may be 99% or less.
[0040] Furthermore, the superabsorbent polymer film of the present disclosure may have a yellowness index of 2.6 or less, 2.5 or less, 2.4 or less, 2.3 or less, 1.9 or less, 1.5 or less, or 1.3 or less when measured according to ASTM D1925 in a thickness range of 1 μm to 500 μm.
[0041] Meanwhile, the superabsorbent polymer film can have a water content of 1% to 15% and a tensile strength of 5MPa or more. Preferably, when the water content is 5% to 15%, the tensile strength of the superabsorbent polymer film can be 10MPa or more, 13MPa or more, 14MPa or more, 19MPa or more, or 22MPa or more, and 50MPa or less, 47MPa or less, 45MPa or less, 40MPa or less, or 35MPa or less. The superabsorbent polymer film that meets the above tensile strength is less prone to damage. Therefore, when it is applied to superabsorbent articles such as diapers, it is not easily damaged and can show excellent hygroscopicity even during the wearer's movement.
[0042] Meanwhile, in order to further improve the air permeability of the superabsorbent polymer film, a pattern having a hole structure can be formed in the superabsorbent polymer film. The shape of the pattern is not particularly limited, and a superabsorbent polymer film having appropriate ventilation and hygroscopicity can be manufactured by adjusting the shape, maximum diameter, average diameter, spacing between holes, and arrangement of holes.
[0043] Alternatively, the air permeability of the superabsorbent polymer film may be further improved by forming a porous structure using a foaming agent such as calcium carbonate in the preparation of the superabsorbent polymer film.
[0044] The above-mentioned super absorbent polymer film can be prepared by a preparation method comprising the following steps: preparing a monomer composition by mixing an acrylic acid-based monomer having an acidic group that is at least partially neutralized, a cellulose-based thickener, a humectant, an internal cross-linking agent, a polymerization initiator, and a solvent; casting the monomer composition on a substrate to form a monomer composition film; forming a hydrogel polymer film by radiating heat and / or light while stretching the monomer composition film; and drying the hydrogel polymer film.
[0045] According to the preparation method, a monomer composition film is prepared from a monomer composition solution having a controlled viscosity by a solution casting method, and the film is polymerized and dried to prepare a super absorbent polymer in the form of a film. In particular, the tensile strength of the super absorbent polymer film to be prepared can be adjusted by applying tension to the monomer composition film in the polymerization step and then stretching it.
[0046] Hereinafter, a method for preparing a super absorbent polymer film will be described in detail.
[0047] The monomer composition includes an acrylic acid-based monomer having an acidic group that is at least partially neutralized, a cellulose-based thickener, a humectant, a polymerization initiator, and a solvent.
[0048] First, the acrylic acid-based monomer is a compound represented by the following Chemical Formula 1:
[0049] [Chemical formula 1]
[0050] R 1 -COOM 1
[0051] In Chemical Formula 1,
[0052] R 1 is a C2 to C5 hydrocarbon group having an unsaturated bond, and
[0053] M 1 It is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.
[0054] Preferably, the acrylic acid-based monomer includes at least one selected from acrylic acid, methacrylic acid, and monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts thereof.
[0055] Herein, acrylic acid-based monomers can be those with at least partially neutralized acidic groups. Preferably, acrylic acid-based monomers partially neutralized with alkaline substances such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, etc. can be used. The degree of neutralization of acrylic acid-based monomers can be 40mol% to 95mol%, 40mol% to 80mol%, or 45mol% to 75mol%. The range of the degree of neutralization can be adjusted according to the final characteristics. Too high a degree of neutralization causes the neutralized monomer to precipitate, and therefore polymerization may not occur easily, while too low a degree of neutralization may deteriorate the absorbency of the polymer.
[0056] In a preferred embodiment, sodium hydroxide (NaOH), potassium hydroxide (KOH), or a combination thereof may be used as the alkaline substance. In particular, when potassium hydroxide is used as the alkaline substance, a superabsorbent polymer film having better flexibility and dimensional stability may be prepared.
[0057] Based on the monomer composition containing the raw material of super absorbent polymer and solvent, the concentration of acrylic acid-based monomer can be about 20% by weight to about 60% by weight, preferably about 40% by weight to about 50% by weight, and it can be appropriately selected in consideration of reaction time and reaction conditions. However, when the concentration of the monomer is too low, the yield of super absorbent polymer is low and there may be problems in economic efficiency. On the contrary, when the concentration is too high, problems such as some monomer precipitation and thus the physical properties of super absorbent polymer may deteriorate may occur during the process.
[0058] Meanwhile, in the present disclosure, a thickener and a humectant are included in the monomer composition so that the monomer composition can be applied in the form of a film by a solution casting method.
[0059] Since the thickener and the humectant are simultaneously included, the monomer composition of the present disclosure may show a viscosity suitable for casting in the form of a film, may maintain an appropriate water content during polymerization after film casting, and the superabsorbent polymer film to be prepared may have high flexibility.
[0060] In the present disclosure, a cellulose-based thickener is used as the thickener, and specifically, at least one selected from nanocellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose and hydroxypropyl methyl cellulose can be used. Preferably, nanocellulose, hydroxyethyl cellulose, or a combination thereof can be used.
[0061] The cellulose-based thickener may be included in an amount of 0.01 parts by weight or more, 0.1 parts by weight or more, 0.2 parts by weight or more, or 0.35 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, 1 part by weight or less, or 0.9 parts by weight or less, based on 100 parts by weight of the solid content in the monomer composition.
[0062] Herein, the solid content in the monomer composition means all components in the composition except the solvent. That is, the solid content means the total content of the acrylic acid-based monomer, the alkaline substance for neutralizing the acrylic acid-based monomer, the cellulose-based thickener, the humectant, the crosslinking agent, the thermal initiator, the photoinitiator, the internal crosslinking agent and other additives.
[0063] If the content of the cellulose-based thickener is less than 0.01 parts by weight based on 100 parts by weight of the solid content in the monomer composition, a sufficient thickening effect may not be ensured, and thus it may be difficult to prepare the monomer composition. On the other hand, if it exceeds 5 parts by weight, the viscosity of the monomer composition becomes too high, making the thickness of the film thicker, and it may be difficult to uniformly control the thickness of the film.
[0064] As the moisturizer, there can be used without limitation substances generally used as moisturizing components in medicines, cosmetics, chemical products, etc. Examples of the moisturizer include at least one selected from polyols having two or more hydroxyl groups in the molecule, citric acid, and citrates.
[0065] Specifically, as the polyol, a C3 to C30 polyol having 3 to 12 hydroxyl groups in the molecule can be used. For example, the polyol can be at least one selected from the following: glycerol; diglycerol; propylene glycol; butylene glycol; sorbitol; polyethylene glycol; polyglycerol-3; polyglycerol-6; polyglycerol-10; and polyglycerol-10 distearate, and derivatives thereof (C3 to C18). Among them, at least one selected from glycerol, diglycerol, ethylene glycol, and sorbitol can be preferably used.
[0066] In addition, citric acid and / or citrates may also be used as moisturizers. Examples of citrates include triethyl citrate, methyl citrate, sodium citrate, trisodium 2-methyl citrate, and the like.
[0067] The moisturizer may be used in an amount of 5 parts by weight or more, 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more, and 70 parts by weight or less, 60 parts by weight or less, or 50 parts by weight or less, based on 100 parts by weight of the acrylic-based monomer.
[0068] If the content of the humectant is less than 5 parts by weight based on 100 parts by weight of the acrylic acid-based monomer, the water content of the monomer composition film is insufficient, so that in the subsequent polymerization and drying process, the film may dry out or break and the flexibility of the superabsorbent polymer film to be prepared may not be achieved. On the contrary, if the content of the humectant exceeds 70 parts by weight based on 100 parts by weight of the acrylic acid-based monomer, there may be a problem of reduced absorbency of the superabsorbent polymer film. Therefore, the content of the humectant preferably satisfies the above range.
[0069] The monomer composition contains an internal crosslinking agent for crosslinking the polymer. As the internal crosslinking agent, those used in the manufacture of existing superabsorbent polymers can be used. The internal crosslinking agent can be a crosslinking agent having one or more ethylenically unsaturated groups in addition to one or more functional groups that can react with the water-soluble substituents of the acrylic acid-based monomer; or a crosslinking agent having two or more functional groups that can react with the water-soluble substituents of the monomer and / or the water-soluble substituents formed by the hydrolysis of the monomer.
[0070] As specific examples of the internal crosslinking agent, C8 to C12 bisacrylamide, bismethacrylamide, poly(meth)acrylates of C2 to C10 polyols, poly(meth)allyl ethers of C2 to C10 polyols, etc. can be used. More specifically, at least one selected from the following can be used: N,N'-methylenebis(meth)acrylate, ethyleneoxy(meth)acrylate, polyethyleneoxy(meth)acrylate, propyleneoxy(meth)acrylate, glycerol diacrylate, glycerol triacrylate, trimethylol triacrylate, polyethylene glycol diacrylate, triallylamine, triaryl cyanurate, triallyl isocyanate, polyethylene glycol, diethylene glycol, and propylene glycol. In one embodiment, polyethylene glycol diacrylate can be used as the internal crosslinking agent.
[0071] Relative to the monomer composition, the internal crosslinking agent can be included in a concentration of 5000ppm or less so that the polymerized polymer can be crosslinked. In one embodiment, the internal crosslinking agent can be included in 100ppm or more, 250ppm or more, or 500ppm or more, and 5000ppm or less, 4500ppm or less, or 4000ppm or less. The internal crosslinking agent can be adjusted to an appropriate content according to the thickness of the superabsorbent polymer film and the range of the desired tensile strength.
[0072] The polymerization initiator used in the method for producing a super absorbent polymer film is not particularly limited as long as it is generally used in the production of super absorbent polymers.
[0073] Specifically, according to the polymerization method, the polymerization initiator can be an initiator for thermal polymerization or an initiator for photopolymerization by UV radiation. However, even when applying photopolymerization method thereto, a certain amount of heat is also generated by UV radiation, and as the polymerization reaction (exothermic reaction) is carried out, some heat is generated. Therefore, the composition can additionally include a thermal polymerization initiator. In a preferred embodiment, a photopolymerization initiator and a thermal polymerization initiator can be used as a polymerization initiator simultaneously.
[0074] Herein, any compound that can form radicals by light such as UV rays may be used as the photopolymerization initiator without limitation.
[0075] For example, the photopolymerization initiator can be one or more compounds selected from the following: benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine and α-amino ketone. In addition, as a specific example of acyl phosphine, commercial lucirin TPO (2,4,6-trimethylbenzoyl diphenyl phosphine oxide), Irgacure 819 (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide) and the like can be used. More different photopolymerization initiators are fully disclosed in "UV Coatings: Basics, Recent Developments and New Application (Elsevier, 2007)" written by Reinhold Schwalm, page 115, and the present disclosure is not limited thereto.
[0076] The concentration of the photopolymerization initiator in the monomer composition may be 10 ppm or more, 20 ppm or more, or 40 ppm or more, and 2000 ppm or less, 1000 ppm or less, 500 ppm or less, or 100 ppm or less. If the concentration of the photopolymerization initiator is too low, the polymerization rate may be slow, and if the concentration is too high, the molecular weight of the superabsorbent polymer may be low and the properties may be uneven.
[0077] In addition, as a thermal polymerization initiator, one or more initiators selected from the following can be used: a persulfate-based initiator, an azo-based initiator, hydrogen peroxide and ascorbic acid. Specifically, as an example of a persulfate-based initiator, sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), ammonium persulfate ((NH4)2S2O8), etc. can be used; and as an example of an azo-based initiator, 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoyl azo)isobutyronitrile, 2,2-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. can be used. More various thermal polymerization initiators are fully disclosed in “Principle of Polymerization (Wiley, 1981)” by Odian, page 203, and the present disclosure is not limited thereto.
[0078] The concentration of the thermal polymerization initiator in the monomer composition may be 10 ppm or more, 100 ppm or more, or 500 ppm or more, and 2000 ppm or less, 1500 ppm or less, or 1000 ppm or less. If the concentration of the thermal polymerization initiator is too low, additional thermal polymerization hardly occurs and the effect of adding the thermal polymerization initiator may be insufficient. If the concentration of the thermal polymerization initiator is too high, the molecular weight of the superabsorbent polymer may become low and the properties may be uneven.
[0079] If necessary, the monomer composition may further contain additives such as a plasticizer, a storage stabilizer, and an antioxidant.
[0080] Alternatively, the monomer composition may further include a foaming agent as an additive. The superabsorbent polymer film prepared from such a monomer composition has a porous structure with multiple pores, thereby exhibiting high air permeability.
[0081] The foaming agent may foam during polymerization and / or drying, and may be, for example, at least one selected from expandable microspheres, expanded microspheres, azo compounds, and inorganic foaming agents. These foaming agents form a large number of pores in the superabsorbent polymer film, and thus may greatly improve the initial absorbency of the superabsorbent polymer film.
[0082] The expandable microsphere may have a structure having a core including a hydrocarbon and a shell surrounding the core and including a thermoplastic resin.
[0083] The hydrocarbon constituting the core of the expandable microsphere may be at least one selected from the following: n-propane, n-butane, isobutane, cyclobutane, n-pentane, isopentane, cyclopentane, n-hexane, isohexane, cyclohexane, n-heptane, isoheptane, cycloheptane, n-octane, isooctane and cyclooctane. Among them, C3 to C5 hydrocarbons (n-propane, n-butane, isobutane, cyclobutane, n-pentane, isopentane, cyclopentane) may be suitable.
[0084] In addition, the thermoplastic resin constituting the shell of the expandable microsphere may be a polymer formed by at least one monomer selected from (meth)acrylate, (meth)acrylonitrile, aromatic vinyl, vinyl acetate, vinyl halide and vinylidene halide. Among them, a copolymer of (meth)acrylate and (meth)acrylonitrile or a (meth)acrylate homopolymer is most suitable for achieving the initial absorbency within the above range.
[0085] The expandable microsphere is a foaming agent that expands by providing heat, and can expand under high temperature conditions in the polymerization and / or drying steps of the monomer to form pores in the superabsorbent polymer film. The expandable microsphere can have expansion characteristics that can be changed according to the components constituting the core and shell, the weight of each component, and its particle size. By adjusting these factors, the pores can be expanded to a desired size and the pore structure of the superabsorbent polymer film can be controlled.
[0086] The average particle size (D50) of the expandable microspheres before expansion may be 2 μm or more, 5 μm or more, 7 μm or more, or 10 μm or more, and 50 μm or less, 40 μm or less, or 35 μm or less. When the expandable microspheres have the average particle size as described above, they may be determined to be suitable for achieving appropriate porosity.
[0087] At this time, the average particle size (D50) of the expandable microspheres can be measured by dispersing the powder to be measured in a dispersion medium, introducing the powder into a commercially available laser diffraction particle size analyzer (e.g., Mastersizer 3000), and then measuring the difference in the diffraction pattern according to the particle size when the laser beam passes through the particles, and then calculating the particle size distribution.
[0088] Whether expandable microspheres can form pores having an appropriate size in a superabsorbent polymer film can be determined by determining the expansion ratio and size after foaming the capsule in air.
[0089] The thickness of the superabsorbent polymer film prepared according to the present disclosure is 0.8 mm or less, preferably 0.001 mm to 0.8 mm, and the pore size is suitably about 10 μm to 500 μm. Therefore, in order to form pores of appropriate size in the superabsorbent polymer film, it is necessary to understand the expansion characteristics of expandable microspheres.
[0090] Specifically, expandable microspheres are applied to a glass petri dish, which is then heated in air for 10 minutes to expand the expandable microspheres. In this aspect, when the expandable microspheres exhibit a maximum expansion ratio of 3 to 15 times, 2 to 12 times, or 1 to 7 times in air, they are suitable for preparing a superabsorbent polymer film having pores of appropriate size.
[0091] In addition, when the expandable microspheres show a maximum expansion size of 150 μm or less in the air, pores with appropriate sizes can be formed. Specifically, when the expandable microspheres show a maximum expansion size of 10 μm to 500 μm, 50 μm to 300 μm, 70 μm to 150 μm, or 75 μm to 150 μm in the air, they are suitable for preparing a superabsorbent polymer film with pores with appropriate sizes.
[0092] In expandable microspheres, expansion may start at 60 to 200°C, 70 to 170°C, or 80 to 165°C, and may reach maximum expansion at 100 to 240°C, 120 to 200°C, or 130 to 190°C.
[0093] Examples of expandable microspheres include the Expancel DU series from Nouryon, such as Expancel 461 DU40, Expancel 461 DU 20, Expancel 031 DU 40, Expancel 053 DU 40, and Expancel 551 DU40; and / or the microsphere F series from Matsunomo, such as microspheres F-AC170D, microspheres F-36, microspheres F-36LV, microspheres F-48, microspheres F-80GS, and microspheres F-50. Preferably, Expancel 031 DU 40 having a core comprising a hydrocarbon and a shell comprising a copolymer of acrylic acid and acrylonitrile and / or microspheres F-AC170D having a core comprising a hydrocarbon and a shell comprising an acrylate copolymer may be used, but the present disclosure is not limited thereto.
[0094] The expanded microspheres are a foaming agent in an expanded state before use, and may be one in which an inorganic material such as talc and / or calcium carbonate is coated on the surface of hollow thermoplastic resin particles.
[0095] The thermoplastic resin may be a polymer formed of at least one monomer selected from the group consisting of (meth)acrylate, (meth)acrylonitrile, aromatic vinyl, vinyl acetate, vinyl halide, and vinylidene halide.
[0096] Preferably, the expanded microspheres may be of the type in which calcium carbonate is coated on the surface of hollow particles of (meth)acrylate and / or (meth)acrylonitrile copolymer.
[0097] The hollow thermoplastic resin particles of the expanded microspheres no longer expand, but shrink when heated. However, the inorganic material on the surface exhibits foamability. Therefore, pores having a size similar to that of the expanded microspheres can be formed, and thus the size of the pores formed in the superabsorbent polymer film can be adjusted by appropriately selecting the particle size of the expanded microspheres.
[0098] Therefore, when the average particle size (D50) of the expanded microspheres is 10 μm or more, 20 μm or more, or 30 μm or more, and 150 μm or less, 130 μm or less, or 120 μm or less, it is suitable for preparing a superabsorbent polymer film having pores of an appropriate size. Here, the average particle size can be measured using the same method as in the expandable microspheres.
[0099] Meanwhile, the foaming temperature of the expanded microspheres may be 130° C. or higher, 140° C. or higher, or 150° C. or higher and 200° C. or lower, or 180° C. or higher.
[0100] Examples of expansion capsules include the microsphere MFL series from Matsunomo, such as MFL-110CAL, MFL-100MCA, MFA HD60CA, MFL HD30CA, and MFL-SEVEN. Preferably, MFL-110CAL in which calcium carbonate powder is coated on the surface of hollow particles of a copolymer of acrylate and acrylonitrile can be used, but the present disclosure is not limited thereto.
[0101] As the azo-based compound, an azoamidine-based compound such as 2,2′-azobis(2-methylpropionamidine) dihydrochloride and 2,2-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]tetrahydrate may be used, and preferably, 2,2′-azobis(2-methylpropionamidine) dihydrochloride may be used.
[0102] As the inorganic foaming agent, at least one selected from calcium carbonate (CaCO3), sodium bicarbonate (NaHCO3), ammonium bicarbonate (NH4HCO3), ammonium carbonate ((NH4)2CO3), ammonium nitrite (NH4NO2), sodium borohydride (NaBH4) and sodium carbonate (Na2CO3) can be used, and preferably, calcium carbonate can be used.
[0103] As the inorganic foaming agent, micron-sized or nano-sized particles with a particle size of 1 nm to 100 μm can be used, and an appropriate type can be selected according to the desired physical properties of the superabsorbent polymer sheet. Herein, the particle size of the inorganic foaming agent can be measured by the above-mentioned laser diffraction method, or can be measured by a scanning electron microscope (SEM).
[0104] In the present disclosure, expandable microspheres, expanded microspheres, azo-based compounds, and inorganic foaming agents may each be used as a foaming agent, or at least one foaming agent may be used in combination with the above-mentioned foaming agents.
[0105] Meanwhile, when at least one of expandable microspheres and expanded microspheres is used as the first foaming agent and at least one of an azo-based compound and an inorganic foaming agent is used as the second foaming agent, the weight ratio of the first foaming agent to the second foaming agent may be 1:0.3 to 1:3 or 1:0.5 to 1:2. When this weight ratio is satisfied, an improved initial absorption rate may be exhibited as described above.
[0106] Meanwhile, the foaming agent may be included in an amount of 0.1 to 10 parts by weight, more preferably 0.5 to 7 parts by weight or 1 to 5 parts by weight, based on 100 parts by weight of the monomer composition.
[0107] If the foaming agent is included in an amount of less than 0.1 parts by weight based on 100 parts by weight of the monomer composition, a porous structure of the super absorbent polymer film resulting from foaming may not be ensured, and thus the effect of improving the initial absorption rate may not be obtained.
[0108] In addition, when the blowing agent is contained in an amount exceeding 10 parts by weight based on 100 parts by weight of the monomer composition, there may be a problem in that the crosslinking degree of the polymer is reduced due to the blowing agent during polymerization. In addition, since the expandable microsphere blowing agent and the expanded microsphere blowing agent have low solubility and low density in a solvent (e.g., water), if the content exceeds 10 parts by weight based on 100 parts by weight of the monomer composition, a phenomenon in which the blowing agent is precipitated from the monomer composition may occur, and thus foaming may not be performed well.
[0109] Most of the above blowing agents actively perform foaming at 80° C. or higher or 100° C. or higher. Therefore, the foaming of the blowing agent may mainly occur in the drying step of the hydrogel polymer film.
[0110] Raw materials, for example, an acrylic acid-based unsaturated monomer, a cellulose-based thickener, a humectant, an internal cross-linking agent, a polymerization initiator, and additives may be prepared in the form of a monomer composition solution dissolved in a solvent.
[0111] Any solvent that can dissolve the components can be used without limitation, and for example, one or more solvents selected from the following can be used alone or in combination: water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide, etc. For example, water can be used as a solvent.
[0112] In the present disclosure, the monomer composition exhibits a viscosity suitable for solution casting by including a cellulose-based thickener and a humectant. Specifically, the viscosity of the monomer composition at 25°C may be 100 mPa·s or greater, 140 mPa·s or greater, or 200 mPa·s or greater and 5000 mPa·s or less, 2300 mPa·s or less, 2000 mPa·s or less, 1500 mPa·s or less, or 1400 mPa·s or less. The viscosity of the monomer composition may be measured with a viscometer (e.g., TV-22 manufactured by TOKI) under the conditions of a rotating shaft #1 and a rotation speed of 1 rpm.
[0113] If the viscosity of the monomer composition is less than 100 mPa·sec, it may be difficult to cast the monomer composition film to a uniform thickness and polymerize it while stretching it. On the contrary, if the viscosity of the monomer composition exceeds 5000 mPa·sec, it is difficult to prepare a uniform monomer composition, and the fluidity of the monomer composition is low, so that the processability is deteriorated and defoaming is difficult.
[0114] A monomer composition is prepared and then cast on a substrate to prepare a monomer composition film. Then, it is polymerized while being stretched to form a hydrogel polymer film. The casting and polymerization of the monomer composition can be performed continuously by a roll-to-roll process.
[0115] First, a monomer composition is applied to a substrate to prepare a monomer composition film.
[0116] Specifically, a polyethylene terephthalate (PET) film, which is commonly used as a release film and at least one surface of which is treated with organic silicon or fluorine hydrophobicity, can be used as the substrate. For example, the substrate can be a siloxane-based polymer or polytetrafluoroethylene. Surface-treated PET film. However, the material of the substrate is not limited thereto, and a suitable substrate may be selected according to the composition and characteristics of the monomer composition.
[0117] For example, a PET film with a hydrophobic treatment on its surface can have a water contact angle of 105° to 110° and a surface energy of 20mN / m to 25mN / m. Such a hydrophobic treated PET film not only facilitates the application of the monomer composition, but also facilitates the peeling of the hydrogel polymer film to be prepared after polymerization, thereby improving the convenience of the manufacturing process. In particular, when the above-mentioned polyether-modified siloxane-based surfactant is included in the monomer composition, the affinity with the hydrophobic treated PET film having the above contact angle and surface energy is high, making it possible to cast with uniform thickness. Therefore, a uniform and thin film can be formed even in a roll-to-roll continuous process, thereby further improving productivity.
[0118] Unlike a general polymer solution casting method in which a solvent is removed after the polymer solution is cast, the present disclosure performs stretching and polymerization processes immediately after applying a monomer composition on a substrate so as not to reduce water content.
[0119] If the water content of the monomer composition film is too low, the components constituting the monomer composition may precipitate before polymerization, and there may be a problem of film breakage after polymerization. Therefore, the water content of the monomer composition film preferably satisfies the range of 30 wt % to 60 wt %, 30 wt % to 50 wt %, or 30 wt % to 45 wt %.
[0120] The thickness of the monomer composition film can be appropriately adjusted according to the desired thickness of the superabsorbent polymer film. Although the thickness of the monomer composition film hardly changes during the polymerization step, when the water content decreases during the drying process of the hydrogel polymer film after polymerization, the thickness may decrease by about 10% to 40%, or 15% to 35%. In view of this, the monomer composition film can be prepared with an appropriate thickness.
[0121] For example, the thickness of the monomer composition film may be 800 μm or less, 600 μm or less, or 500 μm or less and 1 μm or more, 5 μm or more, or 10 μm or more, but is not limited thereto. It may be appropriately adjusted according to the composition of the monomer composition, the specific conditions in the polymerization and drying steps, and the desired thickness of the superabsorbent polymer film.
[0122] Subsequently, polymerization is performed by irradiating heat and / or light while stretching the monomer composition film in the machine direction (MD direction) to form a hydrogel polymer film. Stretching the film during polymerization as described above can control physical properties such as tensile strength of the superabsorbent polymer film to be prepared.
[0123] At this time, the tension applied to the monomer composition film may be 40 N / m or more, 45 N / m or more, 50 N / m or more, or 60 N / m or more, and 100 N / m or less, 90 N / m or less, or 70 N / m or less. If the film is stretched by applying too much tension, the monomer composition film may break or the thickness may be too thin, and if the tension is too small, the physical properties of the film such as tensile strength may not be achieved.
[0124] The polymerization temperature can be appropriately adjusted according to the composition of the monomer composition, but for smooth reaction, it is preferably 40° C. or higher, or 50° C. or higher. In addition, if the temperature is too high, the solvent evaporates and the components constituting the monomer composition may precipitate. Therefore, the polymerization temperature is preferably 90° C. or lower, or 80° C. or lower.
[0125] The water content of the hydrogel polymer film prepared by the polymerization step may be about 20 wt % or more, preferably 25 wt % or more, and 40 wt % or less, or 35 wt % or less. Therefore, the hydrogel polymer film is dried to prepare a final superabsorbent polymer film.
[0126] The temperature of the drying step may preferably be 80° C. to 150° C., or 90° C. to 100° C. Drying within the above temperature range for about 5 minutes to 30 minutes can provide a superabsorbent polymer film having a moisture content of 15 wt % or less, 12 wt % or less, 10 wt % or less, or 9 wt % or less, and 1 wt % or more, 2 wt % or more, 4 wt % or more, or 6 wt % or more.
[0127] Absorbent products
[0128] The absorbent article according to one embodiment of the present disclosure is characterized by including the above-mentioned superabsorbent polymer film between the liquid-impermeable back sheet and the absorbent material. Therefore, the absorbent article can be excellent in feeling by improving the external humidity caused by moisture emitted from the absorbent material absorbing liquid.
[0129] Figure 1 1 is a cross-sectional view showing the configuration of a conventional absorbent article 1. The conventional absorbent article 1 includes a liquid-impermeable back sheet 11, a breathable waterproof film 12, an absorbent material 13, and a liquid-permeable top sheet 14.
[0130] In contrast, Figures 2 to 4As shown in FIG. 1 , the absorbent articles 2, 3, and 4 of the present disclosure include a superabsorbent polymer film 20 between a liquid-impermeable back sheet 11 and a breathable waterproof film 12 and / or between the breathable waterproof film 12 and an absorbent material 13. The superabsorbent polymer film has a thickness (h) of 500 μm or less and has a density of 10 g / m2 measured according to KS F 2611 standard. 2 Up to 100g / m 2 The moisture absorption rate of the absorbent material is high, thereby absorbing the moisture emitted from the absorbent material to the outside to keep the feeling dry during use.
[0131] When Figure 4 As shown in , when the superabsorbent polymer film is placed both between the liquid-impermeable back sheet 11 and the breathable waterproof film 12 and between the breathable waterproof film 12 and the absorbent material 13, the thickness (h) and / or physical properties of each superabsorbent polymer film can be the same as or different from each other.
[0132] Hereinafter, the absorbent article of the present disclosure will be described in detail with respect to each component.
[0133] Super absorbent polymer film
[0134] In the absorbent article of the present disclosure, the above-mentioned superabsorbent polymer film is placed between the liquid-impermeable back sheet and the breathable waterproof film and / or between the breathable waterproof film and the absorbent material.
[0135] As described above, the superabsorbent polymer film has excellent hygroscopicity and can thus significantly improve the humidity outside the back sheet by absorbing moisture emitted from the absorbent material. In addition, since the thickness of the superabsorbent polymer film is 500 μm or less, it exhibits the above-mentioned hygroscopic performance without significantly increasing the thickness of the absorbent article, thereby significantly improving the feeling during use of the absorbent article.
[0136] Liquid impermeable backsheet
[0137] As the liquid impermeable back sheet of absorbent article, a nonwoven fabric prepared by spinning olefin-based resins such as polyethylene and polypropylene can be used. The preparation method of the nonwoven fabric is not particularly limited, but those prepared by processing methods such as air-laid, thermal bonding, spunlace, spunbond, melt-blown and roll bonding (stitchbond) can be used without restriction.
[0138] The pore size of the nonwoven fabric used for the liquid-impermeable back sheet may be 20 μm to 1000 μm, 50 μm to 700 μm, or 10 μm to 300 μm. When the pores of the woven or nonwoven fabric meet the above range, the penetration of liquid is blocked and the penetration of water vapor and air is possible, thereby showing an excellent wearing feeling.
[0139] The basis weight of the liquid-impermeable back sheet is not particularly limited, but is preferably about 10 g / m 2 Up to 25g / m 2 , preferably about 12 g / m 2 Up to 20g / m 2 When the excrement absorbed in the absorbent core is prevented from leaking to the outside, the feeling can be further improved.
[0140] The above-mentioned liquid-impermeable back sheet and superabsorbent polymer film may be laminated by a method such as thermal bonding before manufacturing absorbent articles. Specifically, the superabsorbent polymer film may be laminated on one side of the liquid-impermeable back sheet, and the absorbent article may be manufactured by laminating a breathable waterproof film, an absorbent material, and a liquid-permeable top sheet on the superabsorbent polymer film of the laminate.
[0141] Breathable waterproof membrane
[0142] Meanwhile, the superabsorbent article of the present disclosure includes a breathable waterproof film on the liquid-impermeable back sheet, which allows air to flow more smoothly while being waterproof.
[0143] The breathable waterproof membrane can be prepared by blending a thermoplastic polymer with an additive to prepare a resin composition, and molding the resin composition using cast or expanded film extrusion, or other suitable film forming techniques. The resin composition can have a composition of, for example, 40% to 60% of a thermoplastic polymer and 40% to 60% of an additive. The additive can be various components, such as antioxidants, filler particles, dyes, etc., depending on the desired properties.
[0144] For example, a film prepared by casting a resin composition in which a thermoplastic polymer and an additive are blended is uniaxially or biaxially stretched through three steps of a preheating process, a stretching process, and a heat-setting process to produce a waterproof film having air permeability.
[0145] Thermoplastic polymers include soluble polyolefins such as very low density polyethylene (VLDPE), low density polyethylene (LDPE), high density polyethylene (HDPE), polypropylene, copolymers of ethylene and C3 to C12 α-olefins, copolymers of propylene and ethylene and / or C4 to C12 α-olefins, and propylene-based polymers containing both random propylene units and isotactic propylene units in the polypropylene backbone; block copolymers such as elastomers, polyurethanes, copolyetheresters, polyamide polyether block copolymers, ethylene vinyl acetate copolymers, copoly(styrene / ethylene-butylene), styrene-poly(ethylene-propylene)-styrene, styrene-poly(ethylene-butylene)-styrene, polystyrene / poly(ethylene-butylene) / polystyrene, and poly(styrene / ethylene-butylene / styrene); and the like, but the present disclosure is not limited thereto.
[0146] As an additive, fillers such as calcium carbonate (CaCO3) can be used. Calcium carbonate is a white solid material produced by the reaction of carbonate ions and calcium ions, and a large number of holes can be formed in the film while being combined with a polymer resin. In the present disclosure, considering tensile strength and moisture permeability, in the preparation of a breathable waterproof film, based on the gross weight of the composition for forming a breathable waterproof film, the content of calcium carbonate is controlled within the range of 40% by weight to 45% by weight, and the stretch ratio of the film in the mechanical direction is adjusted to within the range of 2.5 times to 3.5 times. Therefore, the size of the hole formed in the film is adjusted, so that the excrement absorbed in the absorbent material will not leak to the outside, and air or water vapor can more smoothly penetrate the back sheet.
[0147] Specifically, when the content of calcium carbonate and the stretching ratio of the film are adjusted within the above range, a hole having a size (diameter) of about 10 μm to 90 μm, preferably about 40 μm to 60 μm, can be formed in the film. The size of these holes is smaller than the size of water particles (which is 100 μm or more) and larger than the size of steam (which is about 0.001 μm to 0.01 μm). Therefore, the excrement absorbed in the absorbent material will not leak to the outside due to the breathable waterproof film, but the hot air or water vapor in the diaper can be easily discharged to the outside through the breathable waterproof film.
[0148] The air permeability of the breathable waterproof membrane can be 2000g / m 2 24 hours to 5000g / m 2 24 hours, preferably 3500g / m 2 24 hours to 4500g / m 2 ·24 hours. When the air permeability is within the above range, the side effects on the skin caused by humid air can be more effectively prevented.
[0149] The basis weight of the breathable waterproof film is not particularly limited, however, when it is about 15 g / m 2 Up to 22g / m 2 When the film strength is further improved, the air permeability of the film can be adjusted to 3500g / m 2 24 hours to 4500g / m 2 · Within 24 hours. Therefore, the excrement absorbed in the absorbent core can be prevented from leaking to the outside, and air or water vapor can smoothly pass through the back sheet, thereby further improving the wearing feeling of the wearer.
[0150] The above-mentioned breathable waterproof film and superabsorbent polymer film may be laminated by a method such as thermal bonding before manufacturing the absorbent article. As an example, the superabsorbent polymer film is laminated on one side of the breathable waterproof film, and the air permeability of the laminated superabsorbent polymer film and the breathable waterproof film may be 3000 g / m 2 24 hours or more, or 3200g / m 2 24 hours or more, and 5000g / m 2 24 hours or less, 4500g / m 2 24 hours or less, or 4200g / m 2 · 24 hours or less. As described above, the superabsorbent polymer film exhibits excellent hygroscopicity and high air permeability, making it possible to impart hygroscopic properties to absorbent articles without deteriorating air permeability.
[0151] Absorbent Materials
[0152] The absorbent material used in the absorbent article of the present disclosure comprises superabsorbent polymer powder which is an aggregate of superabsorbent polymer particles and pulp.
[0153] As the superabsorbent polymer powder, materials generally used to impart absorption properties to absorbent articles can be used without limitation. The superabsorbent polymer can be, for example, at least one selected from the following: a crosslinked product of an acrylate polymer, a crosslinked product of a vinyl alcohol-acrylate copolymer, a crosslinked product of maleic anhydride grafted polyvinyl alcohol, a crosslinked product of an acrylate-methacrylate copolymer, a crosslinked product of a saponified product of a methyl acrylate-vinyl acetate copolymer, a crosslinked product of a starch-acrylate graft copolymer, a crosslinked product of a saponified product of a starch-acrylonitrile graft copolymer, a crosslinked product of carboxymethyl cellulose, a crosslinked product of an isobutylene-maleic anhydride copolymer, and a crosslinked product of a formaldehyde polymer. Preferably, it can be a crosslinked product of an acrylate polymer.
[0154] The size of the superabsorbent polymer particles constituting the superabsorbent polymer powder may be 100 μm to 1,000 μm, 150 μm to 800 μm, or 300 μm to 600 μm. When the size of the superabsorbent polymer particles is less than 100 μm, the superabsorbent polymer gel swollen by absorbing body fluid may be discharged to the outside of the absorbent article or a gel blocking phenomenon may occur to impair physical properties. When the particle size exceeds 1,000 μm, it is difficult to make the absorbent article thinner.
[0155] The superabsorbent polymer powder may be included in an amount of 10 to 90 wt %, preferably 20 wt % or more, 30 wt % or more, or 40 wt % or more, and 80 wt % or less, or 60 wt % or less, based on the total weight of the absorbent material.
[0156] The pulp used for the absorbent material may be a cellulose fluff pulp formed by comminuting wood pulp. The pulp absorbs liquid quickly and can be used to separate the superabsorbent polymer particles from each other to reduce gel adhesion.
[0157] To this effect, pulp may be included in an amount of 10 to 90 wt %, preferably 20 wt % or more, or 40 wt % or more, and 80 wt % or less, 70 wt % or less, or 50 wt % or less, based on the total weight of the absorbent material.
[0158] Specifically, the superabsorbent polymer may be contained in an amount of about 10 to 90 wt %, preferably about 30 to 60 wt %, based on the total weight of the absorbent core, and the pulp may be contained in an amount of about 10 to 90 wt %, preferably about 40 to 70 wt %, based on the total weight of the superabsorbent material.
[0159] If necessary, in addition to the superabsorbent polymer powder and pulp, the absorbent material may also contain synthetic fibers such as polyethylene fibers, polypropylene fibers, polyester fibers, polyamide fibers, rayon fibers, polyurethane fibers, etc. In this case, the bonding force between the superabsorbent polymer powder and the pulp can be further improved. These synthetic fibers may be used in an amount of 20% by weight or less or 10% by weight or less of the total weight of the absorbent material.
[0160] The method for preparing the absorbent material is not particularly limited. For example, it can be prepared by uniformly mixing superabsorbent polymer powder, pulp and optionally synthetic fibers, extruding the mixture for molding, and then packaging the extruded product with a packaging material such as tissue paper.
[0161] Liquid permeable topsheet
[0162] As the liquid-permeable top sheet, a material which is soft and does not irritate the user's skin while having hydrophilicity so that liquid can quickly penetrate therein can be appropriately used.
[0163] The liquid-permeable top sheet may be, for example, a hydrophilic nonwoven fabric, an anti-blocking film such as an anti-blocking polyethylene film, or a foamed film such as urethane foam, and may be used by laminating one or more thereof.
[0164] Preferably, the liquid permeable top sheet can be a hydrophilic nonwoven fabric made of synthetic or natural fibers such as polypropylene, polyethylene, polyester, polyethylene terephthalate, rayon and cotton. The preparation method of the nonwoven fabric is not particularly limited, and those prepared by processing methods such as air-laid, thermal bonding, spunlace, spunbond, melt-blown and roll-bonded can be used without limitation.
[0165] The fineness of the liquid-permeable nonwoven fabric is not particularly limited. However, when the fineness is in the range of about 1.5 deniers (d) to 6 deniers (d), preferably about 1.5 deniers (d) to 2 deniers (d), skin irritation is minimized when the absorbent article is worn, thereby minimizing the generation of side effects on the skin and improving instantaneous absorption.
[0166] In addition, the length of the fiber is not particularly limited, but when it is about 36 mm to 39 mm, it is possible to improve processability in a carding process for manufacturing a nonwoven fabric and improve surface uniformity of the nonwoven fabric to minimize friction against the wearer's skin.
[0167] The basis weight of the nonwoven fabric formed from these fibers is not particularly limited, but is preferably about 15 g / m 2 Up to 30g / m 2 , preferably about 15g / m 2 Up to 20g / m 2 When applied, it can improve absorption and make the surface softer, thereby minimizing side effects on the skin.
[0168] Method for preparing absorbent article
[0169] The method for preparing the absorbent article is not particularly limited. The absorbent article of the present disclosure can be prepared by laminating the components, i.e., the liquid-impermeable back sheet, the superabsorbent polymer film, the breathable waterproof film, the absorbent material and the liquid-permeable top sheet in an appropriate order, and then fixing them using embossing or fixing them using an adhesive such as a hot melt adhesive.
[0170] For example, when a superabsorbent polymer film is placed between a breathable waterproof film and an absorbent material, an absorbent article can be manufactured by laminating a liquid-impermeable back sheet, a breathable waterproof film, a superabsorbent polymer film, an absorbent material and a liquid-permeable top sheet in this order and then fixing them with an adhesive or embossing.
[0171] Alternatively, the absorbent article can be manufactured by first thermally bonding the superabsorbent polymer film to a liquid-impermeable back sheet or a breathable waterproof film, then laminating them with other components, and then fixing them.
[0172] Meanwhile, when the superabsorbent polymer film is placed between the liquid-impermeable back sheet and the breathable waterproof film, the superabsorbent polymer film is first laminated on one side of the liquid-impermeable back sheet, and then the breathable film is laminated on the upper side of the superabsorbent polymer film (the side not in contact with the liquid-impermeable back sheet). Thereafter, an absorbent material and a liquid-permeable top sheet are laminated on the breathable film, and then fixed to prepare an absorbent article.
[0173] Alternatively, the absorbent article can be manufactured by first laminating a superabsorbent polymer film on one or both sides of a breathable waterproof film, placing them on a liquid-impermeable back sheet, then laminating an absorbent material and a liquid-permeable top sheet, and then fixing.
[0174] The lamination of the superabsorbent polymer film and the liquid-impermeable back sheet and the lamination of the superabsorbent polymer film and the breathable waterproof film can be carried out by thermal bonding, and the temperature and pressure of the thermal bonding can be appropriately adjusted according to the characteristics of the liquid-impermeable back sheet, breathable waterproof film and superabsorbent polymer film used.
[0175] The absorbent article may be a disposable diaper, a sanitary napkin or an incontinence pad.
[0176] Hereinafter, the present invention will be described in more detail with the following preferred embodiments, but these embodiments are provided for illustrative purposes only. It will be apparent to those skilled in the art that various changes and modifications may be made within the scope and spirit of the present invention. Therefore, it is apparent that the changes and modifications are within the scope of the present invention.
[0177] [Example]
[0178] <Preparation of Superabsorbent Polymer Film>
[0179] Example 1-1
[0180] A neutralization solution in which 70 mol % of acrylic acid was neutralized was prepared by mixing 55 g of acrylic acid, 66.6 g of a 45 wt % potassium hydroxide (KOH) solution, and 55 g of water.
[0181] To the neutralized solution were added hydroxyethyl cellulose (HEC, Natrosol 250HR manufactured by Ashland), glycerin, sodium persulfate as a thermal polymerization initiator, and Irgacure 819 as a photopolymerization initiator to prepare a monomer composition having a solid content (TSC) of 54 wt %.
[0182] At this time, HEC was added in an amount of 0.45 parts by weight based on 100 parts by weight of the solid content in the monomer composition, and glycerin was added in an amount of 40 parts by weight based on 100 parts by weight of acrylic acid. In addition, a thermal polymerization initiator and a photopolymerization initiator were added in an amount of 1000 ppm and 80 ppm, respectively, based on the total weight of the monomer composition.
[0183] The viscosity of the prepared monomer composition at 25° C. was measured using a TV-22 viscometer manufactured by TOKI under the conditions of spindle #1 and a rotation speed of 1 rpm, and it was confirmed that the viscosity of the monomer composition was 201 mPa·sec.
[0184] Subsequently, the monomer composition was coated on one side of a polyethylene terephthalate (PET) film to form a 20 μm thick monomer composition film (30% water content). The coating was performed using a comma coater, and the coating roll moved at 0.5 m / min.
[0185] Then, the monomer composition film was irradiated with 370 mJ / cm 2 The monomer composition film was polymerized by UV light to form a hydrogel polymer film. Here, the polymerization reaction was performed while the monomer composition film was stretched by applying a tension of 60 N / m in the MD direction. The thickness of the prepared hydrogel polymer film was 20 μm, and it was determined that there was no significant change compared with the monomer composition film and the water content was 15% by weight.
[0186] Subsequently, the prepared hydrogel polymer film was dried at a temperature of 80° C. for 5 minutes to prepare a super absorbent polymer film (SAP film) having a water content of 10 wt % and a thickness of 17 μm.
[0187] The moisture content was calculated by the following equation using the weight (a) before drying and the weight (b) after drying of the super absorbent polymer film. At this time, the super absorbent polymer film was dried in such a manner that the temperature was increased from room temperature (25° C.) to 150° C. over 5 minutes and then maintained at 150° C. for 15 minutes.
[0188] Water content (%) = (ab) / a*100
[0189] Example 1-2
[0190] A superabsorbent polymer film having a water content of 10 wt % and a thickness of 45 μm was prepared in the same manner as in Example 1-1, except that the thickness of the monomer composition film was 50 μm, the drying temperature of the hydrogel polymer was 80° C., and the drying time was 10 minutes.
[0191] Examples 1-3
[0192] A superabsorbent polymer film having a water content of 10 wt % and a thickness of 149 μm was prepared in the same manner as in Example 1-1, except that the thickness of the monomer composition film was 160 μm, the drying temperature of the hydrogel polymer was 90° C., and the drying time was 10 minutes.
[0193] Examples 1-4
[0194] A neutralization solution in which 70 mol % of acrylic acid was neutralized was prepared by mixing 55 g of acrylic acid, 66.6 g of a 45 wt % potassium hydroxide (KOH) solution, and 55 g of water.
[0195] To the neutralized solution were added an internal cross-linking agent (polyethylene glycol diacrylate) (PEGDA, MW=400, manufacturer: Aldrich), expanded microspheres as a foaming agent (MFL110CAL, manufactured by Matsumoto Yushi-Seiyaku, average particle size: 90 μm to 120 μm, foaming temperature: 160° C. to 170° C.), hydroxyethyl cellulose (HEC, Natrosol 250HR manufactured by Ashland), glycerin, sodium persulfate as a thermal polymerization initiator, and Irgacure 819 as a photopolymerization initiator to prepare a monomer composition having a solid content (TSC) of 40 wt %.
[0196] At this time, the foaming agent was added in an amount of 1 part by weight based on 100 parts by weight of the monomer composition, HEC was added in an amount of 0.45 parts by weight based on 100 parts by weight of the solid content in the monomer composition, and glycerin was added in an amount of 40 parts by weight based on 100 parts by weight of acrylic acid. In addition, a thermal polymerization initiator and a photopolymerization initiator were added in an amount of 1000 ppm and 80 ppm, respectively, based on the total weight of the monomer composition.
[0197] The viscosity of the prepared monomer composition at 25° C. was measured using a TV-22 viscometer manufactured by TOKI under the conditions of spindle #1 and a rotation speed of 1 rpm. As a result, the viscosity of the monomer composition was determined to be 211 mPa·sec.
[0198] Subsequently, the monomer composition was coated on one side of a polyethylene terephthalate (PET) film to form a 160 μm thick monomer composition film (30% water content). The coating was performed using a comma coater, with the coating roll moving at 0.5 m / min.
[0199] Then, the monomer composition film was irradiated with 370 mJ / cm 2 The polymerization was performed by applying a UV light of 1000 nm to form a hydrogel polymer film. Here, the polymerization reaction was performed while the monomer composition film was stretched by applying a tension of 60 N / m in the MD direction.
[0200] Subsequently, the prepared hydrogel polymer film was dried at a temperature of 90° C. for 10 minutes to prepare a super absorbent polymer film (SAP film) having a water content of 10 wt % and a thickness of 153 μm.
[0201] <Preparation of absorbent article>
[0202] Comparative Example 1
[0203] (1) Preparation of liquid impermeable backsheet
[0204] After polypropylene is spun at a high temperature to form a web on which polypropylene fibers are laminated, the web is bonded by a calender roll having embossed protrusions of a predetermined pattern, thereby preparing a liquid-impermeable back sheet (nonwoven fabric, pore size: about 40 μm to 60 μm, basis weight: 12 g / m 2 ).
[0205] (2) Preparation of breathable waterproof membrane
[0206] 50 to 55 wt % of polypropylene, 40 to 45 wt % of calcium carbonate, 1 to 1.5 wt % of a dispersant, 1 to 1.5 wt % of an antioxidant, and 2 to 3 wt % of a colorant are mixed to obtain a waterproof film-forming composition.
[0207] The composition forming the waterproof film is fed to the extruder through a feed hopper and melted. After the molten composition is kneaded in the extruder, it is extruded into a film through a T die and cooled. Then, the film is heated to a stretchable temperature to stretch the film so that the stretch ratio in the machine direction is 2.5 to 3.5 times. After slowly cooling, it is cut to a certain width and length to obtain a basis weight of 17g / m 2 Breathable waterproof membrane (air permeability: 4400g / m 2 24 hours)
[0208] (3) Preparation of absorbent materials
[0209] A deodorant composition was prepared by mixing 8 wt % of salicylic acid, 61 wt % of polyethylene glycol and 31 wt % of cetyl alcohol. Thereafter, the deodorant composition was coated on a substrate having a basis weight of 30 g / m 2 The air-permeable bonded nonwoven sheet is coated with a cotton spunlace. Thereafter, the air-permeable bonded nonwoven sheet coated with the deodorant composition is passed through a hot air drying chamber to evaporate moisture to prepare a core wrapping sheet surface-treated with the deodorant composition.
[0210] 40% by weight of the base weight is 50 g / m 2 The fluff pulp was mixed with 60 wt % of a polyacrylate-based superabsorbent polymer powder having a particle size of 250 to 600 μm (average particle size: 400 μm, CRC: 34 g / g, 0.3 psi AUP: 28 g / g), and the mixture was then wrapped with the prepared core wrap sheet to prepare an absorbent material having a thickness of 3.0 mm.
[0211] (4) Preparation of liquid permeable top sheet
[0212] Use 15g / m 2 A spunbonded nonwoven fabric having a basis weight of 0.05 mm and a thickness of 0.1 mm was used as a liquid-permeable top sheet. The liquid-permeable top sheet was manufactured into a shape that could completely cover the body-side surface of the upper absorbent material so that liquid such as urine could be completely diffused into the upper absorbent material.
[0213] (5) Preparation of absorbent products
[0214] A breathable waterproof film is laminated on one side of the prepared liquid-impermeable back sheet. Then, an absorbent material and a liquid-permeable top sheet are sequentially laminated on the breathable waterproof film and adhered to prepare an absorbent article (disposable diaper).
[0215] Example 2-1
[0216] An absorbent article was prepared in the same manner as in Comparative Example 1, except that the superabsorbent polymer film prepared in Example 1-1 was further laminated between the liquid-impermeable back sheet and the breathable waterproof film.
[0217] Example 2-2
[0218] An absorbent article was prepared in the same manner as in Comparative Example 1, except that the superabsorbent polymer film prepared in Example 1-2 was further laminated between the liquid-impermeable back sheet and the breathable waterproof film.
[0219] Example 2-3
[0220] An absorbent article was prepared in the same manner as in Comparative Example 1, except that the superabsorbent polymer film prepared in Examples 1 to 3 was further laminated between the liquid-impermeable back sheet and the breathable waterproof film.
[0221] Embodiment 2-4
[0222] An absorbent article was prepared in the same manner as in Comparative Example 1, except that the superabsorbent polymer film prepared in Examples 1 to 4 was further laminated between the breathable waterproof film and the absorbent material.
[0223] Embodiment 2-5
[0224] An absorbent article was prepared in the same manner as in Comparative Example 1, except that the superabsorbent polymer film prepared in Example 1-1 was further laminated between the breathable waterproof film and the absorbent material.
[0225] Embodiment 2-6
[0226] An absorbent article was prepared in the same manner as in Comparative Example 1, except that the superabsorbent polymer film prepared in Example 1-2 was further laminated between the breathable waterproof film and the absorbent material.
[0227] Embodiment 2-7
[0228] An absorbent article was prepared in the same manner as in Comparative Example 1, except that the superabsorbent polymer film prepared in Examples 1 to 3 was further laminated between the breathable waterproof film and the absorbent material.
[0229] Comparative Example 2
[0230] An absorbent article was prepared in the same manner as in Example 2, except that 52 μm thick superabsorbent fibers (SAP fibers, Made of Basf) is laminated between the liquid-impermeable back sheet and the breathable waterproof film instead of the superabsorbent polymer film.
[0231] Comparative Example 3
[0232] An absorbent article was prepared in the same manner as in Example 2, except that superabsorbent fibers (SAP fibers, Made of Basf) is laminated between the liquid-impermeable back sheet and the breathable waterproof film instead of the superabsorbent polymer film.
[0233] Comparative Example 4
[0234] An absorbent article was prepared in the same manner as in Example 2, except that a 1.0 mm thick absorbent material (40 wt % fluff pulp, 60 wt % superabsorbent polymer) was laminated between the liquid impermeable backsheet and the breathable waterproof film instead of the superabsorbent polymer film.
[0235] <Experimental Example 1: Evaluation of Physical Properties of Superabsorbent Polymer Film>
[0236] (1) Moisture absorption rate
[0237] The super absorbent polymer film was cut into a size of 15 cm×24 cm, and an aluminum tape was attached to one side of the super absorbent polymer film to prevent moisture, thereby preparing a sample for analyzing moisture absorption performance. Using this sample, the moisture absorption rate of the super absorbent polymer was measured by the following method according to KS F2611:2019 standard.
[0238] 1) Maintain inside a constant temperature and humidity chamber at 25° C. and 50% relative humidity, treat for 12 hours, and then measure the initial mass (W1).
[0239] 2) Maintain inside a constant temperature and humidity chamber at 25°C and 75% relative humidity, absorb moisture for 12 hours, and then measure the mass (W2).
[0240] 3) Calculate the moisture absorption rate according to the following equation.
[0241] Moisture absorption rate (g / m 2 )=(W2-W1) / 0.036
[0242] (2) Tensile strength
[0243] The sample was prepared by cutting the superabsorbent polymer film in a rectangular shape of 20 mm×60 mm so that the cut surface was smooth. Then, the initial clamp gap of the tensile strength measuring device (TAXTplus, manufactured by Stable Micro Systems) was set to 20 mm, and the sample was installed. The sample was stretched at a rate of 0.5 mm per second to measure the force (N) at break, and the value was calculated by dividing the value by the cross-sectional area (mm 2 ) to obtain the tensile strength (MPa).
[0244] <Experimental Example 2: Evaluation of physical properties of absorbent products>
[0245] (1) Evaluation of external humidity
[0246] The absorbent article prepared in one of Examples and Comparative Examples was placed on a glass plate in a room having 50% humidity and 38.7°C temperature, and 350 ml of physiological saline (0.9% NaCl aqueous solution) at 37°C was injected into the liquid-permeable top sheet of the absorbent article.
[0247] After 30 minutes, it was checked whether the vapor condensed on the glass plate. When the vapor condensed, it was evaluated as having external humidity (O), and when the vapor did not condense, it was evaluated as having no external humidity (X).
[0248] (2) Water vapor barrier permeability
[0249] 1000 ml of distilled water was injected into the absorbent article having an area of 25 cm×10 cm prepared in one of the examples and the comparative examples for absorption. Thereafter, the absorbent article absorbing the distilled water was placed in a constant temperature and pressure chamber (humidity: 50%, temperature: 38.7° C.) for 12 hours. Then, the water vapor barrier permeability (g / m 2 12 hours).
[0250] Water vapor barrier permeability (g / m 2 ·12 hours)=(W2-W1) / T
[0251] (In this equation,
[0252] W1 is the weight per area of the absorbent product before constant temperature and humidity treatment (g / m 2 ),
[0253] W2 is the weight per area of the absorbent product after constant temperature and humidity treatment (g / m 2 ),as well as
[0254] T is the time spent for constant temperature and humidity treatment, which is 12 hours.)
[0255] (3) Air permeability
[0256] The superabsorbent polymer film, SAP fiber or absorbent material was thermally bonded to a breathable waterproof film (basis weight: 17 g / m 2 , air permeability: 4400g / m 2 · 24 hours, thickness: 25 μm) to prepare a sample for measuring air permeability, wherein the superabsorbent polymer film is applied between the liquid-impermeable back sheet and the breathable waterproof film or between the breathable waterproof film and the absorbent material in one of the Examples and Comparative Examples.
[0257] A test piece having a size of 150 mm (MD) x 150 mm (CD) was obtained, and the air permeability was measured with a Frazir type air permeability tester in accordance with JIS L 1096. The average value of n = 5 was taken as the measured value.
[0258] [Table 1]
[0259]
[0260] As a result of the experiment, it was determined that Examples 1-1 to 1-4 exhibited excellent moisture absorption and tensile strength. In addition, it was determined that the absorbent articles of Examples 2-1 to 2-7 had significantly improved external humidity without reducing air permeability compared to Comparative Example 1, due to the superabsorbent polymer film interposed between the liquid-impermeable back sheet and the breathable waterproof film or between the breathable waterproof film and the absorbent material.
[0261] In addition, as a result of conducting a simulated wearing test (injecting saline at 37° C. into the liquid-permeable top sheet of the diaper, leaving it at 36.5° C. for 5 minutes, and checking the feel of the back sheet) to evaluate the usability of the diapers in actual use, the diapers of Examples 2-1 to 2-7 showed a warmer and drier feel than the diaper of Comparative Example 1.
[0262] However, when superabsorbent fibers are used instead of superabsorbent polymer films, air permeability remains excellent, but moisture permeability is poor, so the effect of improving external humidity may not be ensured. In addition, when absorbent materials are applied instead of superabsorbent polymer films, external humidity is definitely improved, but air permeability is greatly reduced.
[0263] [Explanation of Reference Numerals]
[0264] 1, 2, 3, 4: Absorbent products
[0265] 11: Liquid impermeable back sheet
[0266] 12: Breathable waterproof membrane
[0267] 13: Absorbent Materials
[0268] 14: Liquid permeable top sheet
[0269] 20: Super absorbent polymer film
Claims
1. A superabsorbent polymer film having a thickness of 500 μm or less and a surface area of 10 g / m2 measured according to KS F2611 standard 2 Up to 100g / m 2 The moisture absorption rate, wherein the superabsorbent polymer film is prepared by a preparation method comprising the following steps: preparing a monomer composition by mixing an acrylic acid-based monomer having an at least partially neutralized acidic group, a cellulose-based thickener, a humectant, an internal crosslinking agent, a polymerization initiator, and a solvent; casting the monomer composition on a substrate to form a monomer composition film; forming a hydrogel polymer film by radiating heat and / or light while stretching the monomer composition film; and drying the hydrogel polymer film.
2. The superabsorbent polymer film according to claim 1, The thickness is in a range of 10 μm to 200 μm.
3. The superabsorbent polymer film according to claim 1, The water content is 1% to 15% and the tensile strength is 5 MPa to 50 MPa.
4. An absorbent article comprising: Liquid-impermeable backsheet; A breathable waterproof membrane; an absorbent material comprising a superabsorbent polymer powder and pulp; and a liquid permeable top sheet, The superabsorbent polymer film according to claim 1 is included between the liquid-impermeable back sheet and the breathable waterproof membrane and / or between the breathable waterproof membrane and the absorbent material.
5. The absorbent article according to claim 4, wherein the superabsorbent polymer film is laminated on one side of the liquid-impermeable back sheet; and / or laminated on one side or both sides of the breathable waterproof film.
6. The absorbent article according to claim 4, wherein the superabsorbent polymer film is laminated on one side of the breathable waterproof film, and The laminated superabsorbent polymer film and breathable waterproof membrane have an air permeability of 3000g / m 2 24 hours to 5000g / m 2 ·24 hours.
7. The absorbent article according to claim 4, The liquid-impermeable back sheet is a nonwoven fabric having a pore size of 20 μm to 1000 μm.
8. The absorbent article according to claim 4, The air permeability of the breathable waterproof membrane is 2000g / m 2 24 hours to 5000g / m 2 ·24 hours.
9. The absorbent article according to claim 4, wherein the absorbent material comprises 10 wt % to 90 wt % of the superabsorbent polymer powder.
10. The absorbent article according to claim 4, The liquid permeable top sheet has a basis weight of 15 g / m 2 Up to 30g / m 2 .
